Legal Personhood of Animals (I): The case for the legal personhood of companion animals. Synthesis of doctrinal developments. - Cédric Riot (Universitat Autonoma de Barcelona. Facultat de Dret, 2018)
Law 2015-177 of February 16, 2015, modifying the French Civil Code, defined animals as « living beings doted with sensibility », which marked an evolution in French Law. Yet neither attributed legal personhood nor provided with a new legal regime, animals remain, except where special laws protect them, covered by the regime of things.